Effects of vitamin C supplementation on recovery from eccentric exercise-induced muscle soreness and damage in junior athletes - Nie, J.; Lin, H. (Journal of Exercise Science & Fitness, 2004)
This study was designed to investigate whether vitamin C (VC) supplementation versus placebo in a randomized and double-blind design would improve recovery from eccentric exercise-induced muscle soreness and damage. 16 trained young males (16.6 ±0.2 years) were randomly assigned into either a placebo (P, n =8) or vitamin C supplementation group (VC, n =8). All subjects were required to perform exercise composed of 10 sets of 15 full-squat jumps at maximum exertion and 30 half-squat jumps with 10-kg weight imposed at waist. Such exercise that consists of eccentric contractions in lower limbs was considered effective in inducing muscle soreness and damage. VC and P groups consumed VC (800 mg) and placebo, respectively, at three hours before and twenty-one hours after the exercise. Venous blood was collected before the first supplementation and immediately (Post-ex), 24 hours (24-hr), and 48 hours (48-hr) after exercise for the analyses of serum creatine kinase (CK), malondialdehyde (MDA) and VC. The level of perceived muscle soreness in leg extensors was also evaluated. It was found that Post-ex and 24-hr serum VC in VC group were higher than the corresponding values in P group while the elevations of 24-hr and 48-hr serum CK were lessened. Nevertheless, the serum MDA and perceived muscle soreness in leg extensors in VC group were not changed from those in P group. Such findings suggested that VC supplementations might protect individuals from eccentric exercise-induced muscle damage with no alteration in oxidative attack of cell membrane. However, it did not lessen perceived muscle soreness.